1954
DOI: 10.1107/s0365110x54000904
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of uracil

Abstract: Uracil crystallizes in the monoelinic system with cell dimensions a = 11.82, b = 12.35, c = 3.62 A, fl = 120 ° and space group P2,/a. The structure was solved by trial and refined by successive threedimensional differential syntheses, a correction being applied to allow for series termination effects. The molecules are held together in layers by NH • • • O hydrogen bonds of length 2-81 and 2.86 A. The planar molecule is found to contain two different C-N distances, two bonds having a probable length of 1-379-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(49 citation statements)
references
References 1 publication
6
43
0
Order By: Relevance
“…The hydrogen bond N3-H3...O4 has an N3...O4 distance of 2-81/~,, an H3...O4 distance of 1.77 A and an N-H...O angle of 179.4°. * Similar dimers occur in the crystal structure of uracil itself (Parry, 1954;Stewart & Jensen, 1967) where the N3...O4 distance is 2.87 A. Note that the hydrogen bonding in the crystal structures of uracil and 1-methyluracil involves 04 as acceptor but not 02.…”
Section: Resultsmentioning
confidence: 86%
“…The hydrogen bond N3-H3...O4 has an N3...O4 distance of 2-81/~,, an H3...O4 distance of 1.77 A and an N-H...O angle of 179.4°. * Similar dimers occur in the crystal structure of uracil itself (Parry, 1954;Stewart & Jensen, 1967) where the N3...O4 distance is 2.87 A. Note that the hydrogen bonding in the crystal structures of uracil and 1-methyluracil involves 04 as acceptor but not 02.…”
Section: Resultsmentioning
confidence: 86%
“…The formation of one specific crystal phase in the uracil compounds stabilized through hydrogen bonds and stacking interactions is a well-known result. 57,58 However, the inclusion of the metal ion, i.e. Na + , in a stable structure is a novel and challenging result.…”
Section: Figurementioning
confidence: 99%
“…This is analogous to the findings that the purine base, guanine, formed almost identical structures on graphite and MoS 2 surfaces [9]. The X-ray crystal study of uracil [18] showed that the molecular packing was in the form of planar sheets parallel to the (001) surface with the uracil molecules arranged in a centrosymmetric dimer configuration. The equivalent dimensions for this arrangement (a = 1.182 nm, b = 1.235 nm and γ = 90 • ) are similar to those determined for uracil on graphite and MoS 2 .…”
Section: Scanning Tunneling Microscopymentioning
confidence: 52%
“…Similarly, the formation of these dimers into the observed herring bone pattern suggested a number of plausible configurations for the monolayer structure. This observation was pointed out by Parry in the original work on the bulk structure [18], in which two trial configurations were proposed to accommodate the space group data. The final structure was resolved by refinement of the electron density maps.…”
Section: Molecular Mechanics Simulationmentioning
confidence: 77%